Manfaat Pengelolaan Suaka Perikanan Terubuk (SPT) Bagi Masyarakat Pesisir di Perairan Bengkalis, Riau: Pendekatan Sistem Sosial-Ekologi: The Benefits of Managing The Terubuk Fish Sanctuary (SPT) for Coastal Communities in Bengkalis Waters, Riau: a Social-Ecological Systems Approach (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
The establishment of the Terubuk Fish Sanctuary (SPT) under Bengkalis Regent Regulation No. 15 of 2010 and the Minister of Marine Affairs and Fisheries Decree No. KEP.59/MEN/2011 has undoubtedly had positive social and ecological impacts. This study aims to assess the social and ecological benefits of the SPT for coastal communities in Bengkalis Waters, Riau. Data were collected through interviews and fishery production analysis based on available data from 2008 to 2016. The presence of Terubuk fish in the waters of Bengkalis, Meranti Islands, and Siak is closely linked to historical and cultural significance. A 10-year production forecast model indicated a decline in Terubuk production, with a predicted decrease of 1.37 tons per year (-0.58%) based on the S-Curve model. Statistical analysis (t-test) also showed no significant difference in Terubuk production before and after the issuance of the regulation (P-Value > 0.005). Overall, Terubuk fishery management in the Riau Province waters has not been effective with only the issuance of area management regulations. Strategic steps are needed, including increasing community involvement in management, enhancing supervision, and enforcing laws to better conserve the Terubuk fishery.